2012
DOI: 10.1021/bc200624a
|View full text |Cite
|
Sign up to set email alerts
|

Glycoengineering Approach to Half-Life Extension of Recombinant Biotherapeutics

Abstract: The potential for protein-engineered biotherapeutics is enormous, but pharmacokinetic modulation is a major challenge. Manipulating pharmacokinetics, biodistribution, and bioavailability of small peptide/protein units such as antibody fragments is a major pharmaceutical ambition, illustrated by the many chemical conjugation and recombinant fusion approaches being developed. We describe a recombinant approach that leads to successful incorporation of polysialic acid, PSA for the first time, onto a therapeutical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…2428 In addition, we have recently shown that chondroitin (CH), a type of glycosaminoglycan (GAG) composed of disaccharide repeats of glucuronic acid (GlcA) and N -acetylgalactosamine (GalNAc), improves the PK of protein drugs. 29 CH-conjugated interferon fully retains its bioactivity, and its plasma activity lasts 100 h after intravenous (iv) injection.…”
Section: Introductionmentioning
confidence: 99%
“…2428 In addition, we have recently shown that chondroitin (CH), a type of glycosaminoglycan (GAG) composed of disaccharide repeats of glucuronic acid (GlcA) and N -acetylgalactosamine (GalNAc), improves the PK of protein drugs. 29 CH-conjugated interferon fully retains its bioactivity, and its plasma activity lasts 100 h after intravenous (iv) injection.…”
Section: Introductionmentioning
confidence: 99%
“…To date, fusion and PEGylation technologies have been successfully used to improve the pharmacokinetic properties of CFCs including half‐life extension. In the fusion approach, clotting factors FVIIa, FVIII and FIX have been linked to several long half‐life moieties including the fragment crystallisable (Fc), recombinant human albumin, carboxy terminal peptide (CTP) and polysialic acid (PSA) . The FC and albumin fusion with rFVIII and FIX have completed their phase 3 studies whilst the CTP and PSA approaches are currently ongoing in their phase 1 and phase 2 clinical developments.…”
Section: Extended Half‐life Clotting Factor Concentratesmentioning
confidence: 99%
“…A new approach aiming to harness the beneficial effects of sialylation has been the incorporation of polysialic acid (PSA) onto therapeutic proteins produced in engineered HEK cells (Chen et al, 2012a). A polysialylated anti-HER2 single-chain variable fragment (scFv) showed an almost 30-fold increase in blood half-life but, unfortunately, PSA attachment also decreased receptor-mediated endocytosis.…”
Section: Protein Glycoengineering To Enhance Efficacy and Therapeuticmentioning
confidence: 99%